KARAKTERISTIK TIPE DASAR DAN PEMANFAATAN PERAIRAN DI SEKITAR PULAU GANGGA, KABUPATEN MINUT - Patty, Wilhelmina (Sam Ratulangi University, 2010)
Coastal resources and space in the coastal around Gangga island, has been used for fishing activities and marine tourism. The purpose of this study to map the profile of bottom waters and to identify patterns sublitoral basic surface waters. The survey was conducted by using the acoustic method of sounding, followed by sediment sampling as well as shooting on the surface of the bottom waters. The result of observation indicates that the basic conditions of slope waters around the island of Ganga slope varies from flat to very steep slopes. Waters of the western Gangga island smaller flat slope found in coastal landform ranging from mangroves, coral reefs and seagrass. Bottom waters to the east of Gangga island to steep slope, with the basic pattern dominated by coral reefs and sand.